OF THE EXTRA-FISCAL ENVIRONMENTAL LEGAL REGIME IN COMPANY WITH LAW No. 14.300/2022 AND THE TAXATION OF PHOTOVOLTAIC ENERGY - de Oliveira Rosa Carneiro, Rafael; Villela Florêncio, Stella (Revista Gênero e Interdisciplinaridade, 2023)
The present work addresses the initial opening of the Brazilian economy regarding photovoltaic energy and its main changes and legislative developments, emphasizing the legal framework of distributed microgeneration and minigeneration of solar energy and its economic, social, environmental, constitutional and tax development , through the deductive research method. Thus, the objective is to review the main legislative provisions regarding the search for an ecologically balanced environment, together with the extrafiscal state duty to encourage, through its market instigating capacity, the obtaining and use of clean energy sources and renewable energy, such as photovoltaics. In these terms, the problematization will be evidenced by Law nº 14.300/2022, which promotes the burden of the beneficiary consumer of photovoltaic energy, in view of new tariffs. Finally, it is concluded that the state regulatory capacity of the market through the edition of extrafiscal norms is a basic element for the promotion and promotion of alternative sources of clean energy, in favor of a sustainable environment, not ruling out the need for pursuit of tax equity, in the light of the principle of ability to pay.